The Impact Of Employee Selection On Work Productivity: Case Study At PT. Prima Alloy Steel Universal Gedangan - Enny Istanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In efforts to manage existing resources, many problems are encountered, because not all resources are available in abundance. There may be difficulties in obtaining these resources, such as funding sources. Machines and also limited management skills. One of these resources or resource factors is the human factor. Without humans it is impossible to carry out an activity, therefore, to ensure the continuity of the business activity, it is very necessary to pay attention to human resources as a determining factor for the smoothness and success of the company, in achieving the company's predetermined goals. Therefore it requires special handling in its management, both regarding planning, procurement and development. To procure these workers, good selection is needed, even though there are workers who need work and on the other hand the company needs them, the company does not just attract workers haphazardly. If the process of procuring workers in a company is not paid enough attention, it is likely that the workers obtained will be less capable and skilled, and less able to be developed. This can lead to many errors in carrying out tasks which will affect work productivity within the company. To avoid the losses mentioned above, companies must try to obtain capable and skilled workers and must make the best use of them.